Attitudes Regarding the Use of Ventilator Support Given a Supposed Terminal Condition among Community-Dwelling Mexican American and Non-Hispanic White Older Adults: A Pilot Study - M. Rosina Finley; Johanna Becho; R. Lillianne Macias; Robert C. Wood; Arthur E. Hernandez; David V. Espino (The Scientific World Journal)
Purpose. To determine the factors that are associated with Mexican Americans’ preference for ventilator support, given a supposed terminal diagnosis. Methods. 100 Mexican Americans, aged 60–89, were recruited and screened for MMSE scores above 18. Eligible subjects answered a questionnaire in their preferred language (English/Spanish) concerning ventilator use during terminal illness. Mediator variables examined included demographics, generation, religiosity, occupation, self-reported depression, self-reported health, and activities of daily living. Results. Being first or second generation American (OR = 0.18, CI = 0.05–0.66) with no IADL disability (OR = 0.11, CI = 0.02–0.59) and having depressive symptoms (OR = 1.43, CI = 1.08–1.89) were associated with preference for ventilator support. Implications. First and second generation older Mexican Americans and those functionally independent are more likely to prefer end-of-life ventilation support. Although depressive symptoms were inversely associated with ventilator use at the end of life, scores may more accurately reflect psychological stress associated with enduring the scenario. Further studies are needed to determine these factors’ generalizability to the larger Mexican American community.